Recent advances in solid phase extraction methods for the determination of bisphenol A and its analogues in environmental matrices: an updated review - Mohd Ali, Nur Farahin; Sajid, Muhammad; Abd Halim, Wan Ibrahim Thani; Mohamed, Ahmad Husaini; Mohamad Zain, Nur Nadhirah; Kamaruzaman, Sazlinda; Mohamad Hanapi, Nor Suhaila; Wan Ibrahim, Wan Nazihah; Yahaya, Noorfatimah (Elsevier, 2023)
Bisphenols in the natural environment have recently attracted global attention as they pose many potential hazards to both human health and the aquatic ecosystem. Due to their trace-level presence, the direct determination of bisphenols in food and water matrices is quite challenging. Most of the existing analytical instrumentation cannot directly handle complex sample matrices. Thus, sensitive, effective, rapid, and simple methods are required to extract and concentrate these compounds. The sample preparation is crucial in the overall chemical analyses. It is essential to isolate and concentrate the analytes of interest from the given matrices to ensure their suitability for separation and detection systems. Many new methods have been recently developed to overcome the limitations of the conventional sample preparation methods. This review provides a detailed background of bisphenol A and its analogues, along with recent advancements in their extraction from various matrices using solid-phase extraction techniques. A critical overview of the analysis type is also presented.